من الموصولات الاسمية المشتركة (مَنْ، مَا) دراسة نحوية تطبيقية من خلال القرآن الكريم - الشريقي, ربيعة أبوعجيلة (Al-Qurtas, 2023)
من الموصولات الاسمية المشتركة (مَنْ، مَا) دراسة نحوية تطبيقية من خلال القرآن الكريم